2018
DOI: 10.1007/s12020-018-1630-4
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of acromegaly in Italy: analysis from a large longitudinal primary care database

Abstract: This epidemiological study on acromegaly carried out using a large GP-based database, documented a disease prevalence of about 7 cases per 100,000 inhabitants. As expected, acromegaly was associated with a number of comorbidities (mainly hypertension and type II diabetes mellitus) and a high rate of patients' hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
6
14
0
3
Order By: Relevance
“…The prevalence and incidence of acromegaly in Japan in the present study were comparable to those reported in other countries by previous studies [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. A nationwide hospital survey in South Korea, a country adjacent to Japan, provided with the corresponding rates of 2.8 cases per 100,000 and 0.4 cases per 100,000 [14].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The prevalence and incidence of acromegaly in Japan in the present study were comparable to those reported in other countries by previous studies [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. A nationwide hospital survey in South Korea, a country adjacent to Japan, provided with the corresponding rates of 2.8 cases per 100,000 and 0.4 cases per 100,000 [14].…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies on the epidemiology of acromegaly have reported the prevalence of 1.8-13.7 per 100,000 people, the annual incidence of 0.2-1.2 per 100,000 people, and the ratio of males to females is roughly 1:1 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In Japan, a questionnaire survey of large hospitals nationwide in 1993 reported 815 cases with acromegaly within the past five years [24], but few recent epidemiological data on acromegaly have been reported.…”
mentioning
confidence: 99%
“…Two thirds were diagnosed before 65 years of age, therefore we cannot exclude an in uence of disease duration on our results. Indeed, it is well consolidated that disease duration in uences comorbidities development and worsening [32]. ACRO group was predominantly represented by females, in agreement with recent Italian series [20,21,33].…”
Section: Discussionsupporting
confidence: 82%
“…1,2 The incidence is approximately 3 cases per 1 million persons per year, though more recent estimates report an increased incidence (about 11 per million person-years). [3][4][5][6] As far as prevalence, some studies estimate that the disease affects 40-70 patients per million of the general population, or even more (86-240 per million). 7,8 Comorbidities and mortality risk in acromegalic patients are related to time of exposure to GH and IGF-1 excess.…”
Section: Introductionmentioning
confidence: 99%